Selección de Alternativas para el Suministro de Gas Natural en Colombia empleando el Proceso Analítico Jerárquico - Becerra Fernández, Mauricio; Rodriguez Yee, Ricardo (Ingeniería, 2017)
Context: Colombia consumes natural gas in different sectors, especially in the ones that are residential and vehicular transport. Gas consumption serves as backup for power generation in situations of reduced hydroelectric capacity. Nowadays, gas reserve levels have been reduced and it is essential to ensure the uninterrupted supply of the resource. To achieve such objective, there are some alternatives which are difficult to implement at the same time, given the limited financial budget and implementation times that they demanded. In this way, several studies have advanced in the application of models to prioritize alternatives for both supplying power and reducing emissions in the generation, especially regarding the evaluation of energy sources and technology selection for supply. Method: The Analytic Hierarchy Process (AHP) based in the Delphi method to define preferences according to the experts judgment, was applied to evaluate the selection of alternatives supply of natural gas in Colombia, considering technical, environmental and social criteria, which is reliable and policy oriented to guarantee supply of resources in the country. Results: Once the model was applied, we evaluated the criteria and alternatives for infrastructure to support gas supply, finding that reliability is the most relevant criterion as well as alternative of building the ‘Regasification Pacific Plant’ followed by the construction of the ‘Buenaventura-Cali pipeline’ and the ‘Storage Plant in Bogotá'. Conclusions: As the results indicate, in Colombia efforts should be focus on imports of the resource through the construction of regasification plants and pipelines to facilitate transport inland to demand points. The latter may help decision makers facing various alternatives to ensure the supply of this resource, which is relevant to various economic sectors, including generation of electricity in the country. Language: Spanish